Comparative analysis of customer satisfaction on Islamic and conventional banks in Malaysia - Md Saad, Norma (Canadian Center of Science and Education, 2012)
Customer satisfaction is critically important for banks to stay competitive as the customer is the ultimate source of income for any organization. Islamic banking system and conventional banking system are considered as rival systems working in the same banking industry. In order for Islamic banks to compete successfully with conventional banks, Islamic banks must give extremely high consideration to their primary customers. Whenever either Islamic banks or conventional banks offer any product or service, its success depends upon the customer satisfaction towards that product or service. This study examines the level of customer satisfaction on Islamic banks as well as conventional banks in Malaysia. It also investigates the relationship between different demographic variables and the satisfaction of customers. A sample of 1,153 respondents from various cities representing different states in Malaysia was selected. The results in this study suggest that customers are mostly satisfied with the quality of services which include competency, friendliness, and efficiency of the staff of the Islamic and conventional banks.